Performance Evaluation of a Modified Compound Parabolic Concentrating Collector with Varying Concentration Ratio - Akhter, J. (Taylor and Francis Ltd., 2021)
Thermosyphon based evacuated tube solar collectors have seen exponential growth in the last few decades for domestic hot water applications. The output temperatures of such collectors can be increased by integrating evacuated tube receivers with compound parabolic concentrators (CPCs) to meet many industrial heat loads. This paper presents a new concept of increasing concentration of solar radiation along the length of an evacuated tube receiver coupled with a modified CPC with 52.5° and 38.5° acceptance half-angles at the inlet and outlet sides respectively. The effect of varying concentration ratio in the longitudinal direction is analyzed in terms of increasing heat flux and temperature gradient between the inlet and outlet of the receiver. Monte Carlo ray-tracing analysis confirmed a gradual increase of power density along the length of the receiver paired with the modified CPC. The daily average energy collection by the modified CPC was comparable with that of equal aperture area CPC with a fixed concentration ratio along its length. The experimental results demonstrated about a 15 higher temperature gradient in the case of CPC with a varying concentration ratio as compared to equal aperture area CPC with a fixed concentration ratio single-phase thermosyphon flow. © 2020 Taylor & Francis Group, LLC.